Prevalence of antibiotic resistance genes in resistome of adult residents of Arkhangelsk with regard to the severity of COVID-19 - E. A. Krieger; A. V. Pavlenko; Yu. P. Esin; A. L. Arkhipova; S. N. Kovalchuk; L. L. Shagrov; N. I. Belova; N. P. Tsyvareva; A. V. Kudryavtsev; E. N. Ilina (Журнал инфектологии)
Objective: to estimate the prevalence of antibiotic resistance genes in the resistome of adult residents of Arkhangelsk with regard to the severity of the novel coronavirus infection (COVID-19).Materials and methods. A cross-sectional study was conducted between October and November 2022 (2.5 years after the start of the COVID-19 pandemic) on a random sample (N=455) of Arkhangelsk population aged 42-76 years. The data collection involved a questionnaire survey, assessment of immunoglobulins G to S-, S2, N-proteins of SARS-CoV-2 and detection of antibiotic resistance genes in fecal samples by polymerase chain reaction.Results. Almost all participants (98.5%) had at least one antibiotic resistance gene, the resistance determinants to three classes of antibiotics simultaneously were detected in 5.6%. The prevalence of resistance genes to macrolides was 98.5%, to beta-lactams – 29.0%, and to glycopeptides – 16.0%. Antibiotic resistance genes to beta-lactams were more prevalent among participants who had previously been hospitalized for COVID-19 (44.8%) and among those having had frequent acute respiratory infections (50.0%). Individuals vaccinated against SARS-CoV-2 (26.6%) and participants with cardiovascular diseases (17.0%) were less likely to have beta-lactam resistance genes.Conclusion. The high prevalence of antibiotic resistance genes has been revealed in the resistome of adult residents of Arkhangelsk. We determined the association between resistance to beta-lactams and COVID-19 severity. The study results could be used to improve the protocols of antibiotic therapy and to guide a decision-making related to the antibiotic prescription in adults.